Open Government Analysis: A Study in Brazil and Mexico - Syed Agung Afandi; Rizki Erdayani; Hijratul Aswad; Muslim Afandi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study aims to analyze open government in Brazil and Mexico. Both are Latin American countries that initiated the Open Government Partnership. Qualitative approaches, bibliometric analysis methods, and content analysis methods are used in this study. The data for this study were obtained from the open government policy documents of both countries and sourced from the Google Scholar database. The findings of this study indicate that the open government of Brazil and Mexico is unpopular and therefore not in line with the main objective of the Open Government Partnership to campaign for open government. The dominant issues in both countries include e-government, public policy, health, accountability, transparency, access, and participation. While the current issue is related to climate change. These issues show the urgency and potential future contribution to open government in both countries. In its efforts to campaign for open government, Brazil has set 130 of their commitments, while Mexico focuses on 87 commitments. Brazil has continuously updated their commitments, while Mexico, after 2022, does not have a commitment that is a major part of the Open Government Partnership. However, all commitments from both countries have the potential to create a more open government. The findings of this study serve as recommendations for stakeholders in both countries, including Latin American countries and all members of the Open Government Partnership.